YOUTUBE AS A SOURCE OF INFORMATION ABOUT UNPROVEN DRUGS FOR COVID-19: the role of the mainstream media and recommendation algorithms in promoting misinformation - Soares, Felipe; Salgueiro, Igor; Bonoto, Carolina; Vinhas, Otávio (Brazilian journalism research, 2022)
ABSTRACT - In this study, we address how YouTube videos promote misinformation about hydroxychloroquine in Brazil. We follow two research questions. RQ1: How is pro-hydroxychloroquine content propagated on YouTube? RQ2: How does YouTube’s recommendation system suggest videos about hydroxychloroquine on the platform? We use mixed methods (content analysis and social network analysis) to analyze 751 YouTube videos. We found that most pro-HCQ videos in our dataset are posted by mainstream media channels (RQ1) and that YouTube was more likely to recommend pro-HCQ videos than anti-HCQ videos (RQ2). Consequently, the Brazilian mainstream media and YouTube’s algorithms fueled the spread of pro-HCQ content. RESUMO – Neste estudo, abordamos como os vídeos no YouTube promovem desinformação sobre a hidroxicloroquina no Brasil. Seguimos duas questões de pesquisa. RQ1: Como o conteúdo pró-hidroxicloroquina é propagado no YouTube? RQ2: Como o sistema de recomendação do YouTube sugere vídeos sobre hidroxicloroquina na plataforma? Usamos métodos mistos (análise de conteúdo e análise de redes sociais) para analisar 751 vídeos do YouTube. Descobrimos que a maioria dos vídeos pró-HCQ em nosso conjunto de dados foi postado pelos principais canais de mídia (RQ1) e que o YouTube era mais propenso a recomendar vídeos pró-HCQ do que vídeos anti-HCQ (RQ2). Consequentemente, a imprensa tradicional brasileira e os algoritmos do YouTube fomentaram a disseminação de conteúdo pró-HCQ. RESUMEN – En este estudio, abordamos cómo videos en YouTube promueven desinformación sobre la hidroxicloroquina en Brasil. Seguimos dos preguntas de investigación. RQ1: ¿Cómo se propaga el contenido pro-hidroxicloroquina en YouTube? RQ2: ¿Cómo el sistema de recomendaciones de YouTube sugiere videos sobre hidroxicloroquina en la plataforma? Utilizamos métodos mixtos (análisis de contenido y análisis de redes sociales) para analizar 751 videos de YouTube. Descubrimos que la mayoría de los videos pro-HCQ en nuestro conjunto de datos son publicados por los principales canales de medios de comunicación (RQ1) y que era más probable que YouTube recomendara videos pro-HCQ que videos anti-HCQ (RQ2). En consecuencia, los principales medios de comunicación brasileños y los algoritmos de YouTube impulsaron la difusión de contenido pro-HCQ.